Synthesis of silver nanoparticle with Colocasia esculenta (L.) stem and its larvicidal activity against Culex quinquefasciatus and Chironomus sp - Arghadip Mondal; Amita Hajra; Wasim Akram Shaikh; Sukalyan Chakraborty; Naba Kumar Mondal (Asian Pacific Journal of Tropical Biomedicine, 2019)
Objective: To synthesize silver nanoparticles with Colocasia esculenta as a reducing agent and to evaluate their effect against Culex quinquefasciatus and Chironomus sp. Methods: The aqueous extract of Colocasia esculenta stem was used for nanosynthesis. The synthesized nanoparticles were characterized by UV-Vis spectrophotometry, Fourier-transform infrared spectroscopy, scanning electron microscope, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and Zeta potential studies. The toxicity of Colocasia esculenta stem extract and the synthesized silver nanoparticles was evaluated against the larval stages of target human filarial vector Culex quinquefasciatus and non-target Chironomus sp. Results: Scanning electron microscopy and transmission electron microscopy studies revealed almost spherical shape of the synthesized silver nanoparticles with size ranging from 13-50 nm. After 24 hours of exposure, the LC50 and LC90 of the plant extract against 4th instars larvae of Culex quinquefasciatus were 745.56 mg/L and 1 258.28 mg/L, respectively, which were higher than those of synthesized silver nanoparticles (5.17 mg/L and 17.32 mg/L after 24 h; 1.58 mg/L and 13.01 mg/L after 48 h). In addition, the LC50 and LC90 of silver nanoparticles against Chironomus sp. were 9.71 mg/L and 23.15 mg/L after 24 h as well as 2.38 mg/L and 19.49 mg/ L after 48 h, respectively. Conclusions: The aqueous stem extract of Colocasia esculenta is a good agent for synthesis of silver nanoparticles, which are almost spherical with size less than 30 nm. The synthesized nanoparticles show good larvicidal activity without any harmful effect on non-target species.